Synthesis and characterization of silicon oxide and silicon carbide nanostructures / Majid bin Salim bin Mohammed Al-Ruqieshi - Al-Ruqieshi, Majid Salim Mohammed (2010)
Silicon oxide nanostructures have attracted extensive interests in recent years due to their physical and optical properties. SiOx nanostructures are synthesized by catalytic and non-catalytic approaches. With catalytic approach, long and uniform amorphous silicon oxide nanowires, nanofibers (comet and tree like), nanocakes and nanocages were synthesized on Si substrate by carbothermal evaporation reactions of TiO2 at high temperature. The SiOx nanowires were about 13 nm to 243 nm in diameters and 194 nm to several microns in length and the nanofibres with diameter between 8 nm to 30 nm and around 50 nm to 2.5μm in length. The diameter and density of SiOx nanostructures were modified by controlling the size, distribution and thickness layer of the Au particles on substrate surface by annealing process. The average lowest diameter was found as 37 nm with 6.8 nm gold layer thickness. In non-catalytic part the obtained SiOx nanostructures diameters were about from 60 nm to 300 nm and several microns in length. The formation of cracks on the silicon substrate surface found to be due to the evaporation of silicon monoxide at ≥900°C. It was found that increased temperature, C:TiO2 ratio and deposition time increases the yield of the growth of SiOx nanostructures. The highest yield for SiOx nanowires growth is obtained at 10 sccm Ar flow rate. The XRD and FTIR results confirmed that the obtained SiOx nanowires are amorphous. The SiOx nanostructures PL consist of UV peak centred at 350 nm (3.54 eV), one wide peak in the blue and green regions (400-600 nm) and red band cantered at 730 nm. A broad emission band from 290 to 600 nm is observed in the photoluminescence (PL) spectrum of these nanostructures. There are four PL peaks: I one UV, two emissions in green bluish region and one red emission. PL higher intensity in the case of non catalytic wires is due to the higher oxygen vacancies. We believed that the assistance of carbon is the most important factor to enhance the fabrication of beta-type silicon carbide nanowires. The grown β-SiC nanowires were aligned in shape with almost same height and with diameter ranged between 40 to 500 nm. The majority of crystal planes are planes of β-SiC (111) with other less intensity of (200), (220) and (311). The effect of parametric studies (substrate location, Ar and O2 flowrate, rapid heating rate) on the growth of β-SiC nanowires was carried out. The FTIR results reveal that the most chemical bonds were single Si-C, which can be related to the obtained β-SiC nanostructure.